A binder from alkali activation of FCC waste: Use in roof tiles fabrication - Mas, María A.; Tashima, Mauro M. [UNESP]; Payá, Jordi; Borrachero, María; Soriano, Lourdes; Monzó, José M. (Trans Tech Publications, 2016)
Nowadays, scientific community is looking for alternatives to reduce the problem of CO2 emissions, making more sustainable binders and reusing wastes from other industries. In this line, the technology of geopolymers was born, in which, binders based on alkali-activation can be produced entirely or almost entirely from waste materials. In alkali-activation a source of aluminosilicate is dissolved by a highly alkaline solution previous to precipitation reactions that form a gel binder. The use of alumino-silicate minerals such as metakaolin, blast furnace slag and fly ash to produce alkali-activated cements has been extensively studied and it's increasing the interest in investigating the suitability of using other materials. Different wastes containing silica and alumina, such as hydrated-carbonated cement, glass, fluid catalytic cracking catalyst residues (FCC) have been activated. The aim of this study is to verify if the use of geopolymers is compatible with the manufacturing technology of typical building elements, in this case roof tiles. Mechanical properties of mortars and roof tiles using as source of aluminosilicates FCC have been studied, with different mixtures and variating the proportions of NaOH and waterglass. Compressive strength development was evaluated in mortars cured at 20C for 7 and 28 days and flexural strength, impermeability and impact resistance were evaluated in roof tiles. The results obtained demonstrated the feasibility on the use of geopolymers in the design of new products with less CO2 emissions and then the contribution to the sustainability in the construction sector.
Keywords: Alkali activation; Fluid catalytic cracking catalyst (FCC); Roof tiles; Waste